Inovasi Pengembangan Minuman Mocktail Berbasis Buah Campoleh dan Bahan Rempah Lokal untuk Peningkatan Pendapatan Masyarakat Kampung Adat Cireundeu - Nova Yudha Andriansyah Putra; Dyah Mustika Wardani; Mezi Julian (Lembaga Pengembangan Kinerja Dosen, 2024)
Cireundeu Traditional Village, which is known for its rich traditions and natural resources, has great potential in utilizing campoleh fruit and local spices. However, local communities have not fully utilized this potential in developing products that can increase their income. Mocktail drinks, as an increasingly popular non-alcoholic alternative, offer opportunities for product innovation that can increase market appeal and boost local economies. The aim of this activity is to develop mocktail drinks based on campoleh fruit and innovative local spices. The method for this activity is through identifying campoleh fruit varieties available in the Cireundeu Traditional Village and local spices that can be used in mocktail drinks, then holding training for the local community regarding mocktail making techniques, hygiene and marketing aspects by helping the community in designing marketing strategies and packaging. products, and distribution to increase market reach. This project is expected to not only improve the economy of the Cireundeu Traditional Village community through product innovation but also preserve and promote cultural riches and local resources. By utilizing the potential of campoleh fruit and local spices, communities can create products that are attractive and highly competitive in the market, while strengthening the identity and economic independence of their community. The output of this PM is Pres Release, IPR and PM Journal.